THE IMPLEMENTATION OF A VIDEO BLOG (VLOG) TO ENHANCE STUDENTS’ SPEAKING SKILLS - Putri Rindu Kinasih; Angelique Nitsa (Universitas Wiralodra, 2023)
Despite its importance, teaching speaking in English classes has become challenging. First, most teachers cannot encourage students to speak English because of a lack of time. Secondly, as a result of their fear of making mistakes, the students rarely engage in English-speaking classes. Similarly, the writers identify this issue when teaching speaking to second-semester English Language and Literature (BBI) students at Universitas Bunda Mulia. The students are reluctant to speak out in class and, when they do, they talk in a very low voice. On top of that, the writers also noticed that the students rely so much on their notes. This study aims to study to what extent vlogs help students to speak English in a class by using Classroom Action Research (CAR). There are 71 participants from the first semester, majoring in English Language and Literature (BBI). The data is taken from questionnaires result, and interviews with samples of the participants. In addition, a ratter is invited for collaboration to assess the pre-test and post-test. The study reveals that vlogs in speaking classes improve students' test scores by encouraging open communication and enhancing confidence, professionalism, and improvability. It helps students practice speaking English in front of an audience.